Concentration of milk oxylipins after heat and homogenization treatments - Thum, Caroline; Cirelli, Amanda; Otoki, Yurika; Ozturk, Gulustan; Taha, Ameer Y.; McNabb, Warren C.; Roy, Nicole C.; Leite Nobrega de Moura Bell, Juliana Maria (Frontiers in Food Science and Technology, 2023)
Heat treatment and homogenization of milk are common processing steps intended to reduce microbial load for safe human consumption, and to avoid creaming, respectively. Although the effects of combined pasteurization and homogenization on free fatty acids (FFA) and lipid oxidation markers such as hydroperoxides, and thiobarbituric acid reactive species (TBARS) have been well characterized, their effects on primary oxidized fatty acids known as oxylipins have not yet been determined. This study aimed to determine the effects of two heat treatments: milk pasteurization [high-temperature short time, 72°C for 15 s (HTST)] and sterilization [ultra-high temperature, 135°C for 3 s (UHT)] with or without homogenization (10, 17 or 24 MPa) on FFA (%), primary (hydroperoxides and oxylipins) and secondary oxidation compounds (TBARS). Heat treatments alone significantly reduced most oxylipins compared with raw milk, but did not alter % FFA, hydroperoxide, and TBARS levels. The combination of UHT and homogenization at 24 MPa increased % FFA, hydroperoxide value, and some oxylipins, compared to raw milk and other treatments. Overall, the combination of heat treatment and homogenization significantly increased oxylipin formation compared with heat treatment alone.